Stability studies of papaya pectinesterase - Asbi, B.A; Ghazali, H.M; Yaakob, Che Man; Selamat, Jinap (1995)
Stability studies were carned out on the purilied papaya (Curiro pupqa L. var. UM~UI) pectincsterase (EC 3.1. I. I1 1. The enzyme preparation was stabk at 4’C in 0-02~ sodium phosphate butTer (pH 7.5) solution containing 0.2~ N&l and O-O% sodium azide and the loss in activity was less than 5% after storage (or I year. The thermoslability studia showed that enzyme was more heat-stable at pH 7-5 thao at pH 4. After heating al 60°C for 5 min. 65 6 and 82% activity still remained at pH 4 and pH 7-5. respectively. Ii war completely inactivated by heating for 5 mitt at 70 and 75°C al pH 4 and pH 7.5, respectively. The D values (time to inactivate W%, or the enzyme) at 55.60, 65 and 70°C at pH 4.0 were estimated 10 bo 112.14. 23.78.8.33 and I.71 min. respectively. Lower inactivalion rates were ohscrvcd for pH 7.5. whh lhe D values ranging from 143.27 to I.67 min for tcmper4tures between 60 and 7W. The 2 values, which indicate lhc rise in temperature necessary *o obarvc a IO-times faster rdte of heat-inaclivdtion. were estimated lo he 7%‘C and S,38’C at pH 7.5 and pH 40. respectively. The inactivation energies and Qlo values were calculated as 256.9 W/m01 and 15.59 at pH 4.0 and 284.76 kllmol and 19.21 at pH 7 5. respectively. pH stability arudics showed that the enzyme was stable from pH Cl I abler exposure of ihe enzyme LO these pHs far 24 h at 3WC. More than 85% of the activity was retained in all of these casts. However. at pH I and 12. the enzyme was unstable nnd it complctcly lost ib activity after 24 h of incubation at 30°C.